1,7-Sigmatropic rearrangement in 1,2-dihydro and 1,2,3,4-tetrahydroquinoline synthesis using marine sponge/H2C2O4 as a catalyst - Mohammad Reza Shushizadeh (Arabian Journal of Chemistry, 2015)
Marine sponge/oxalic acid was found to be an efficient catalyst for the imino Diels–Alder reaction of synthesized N-aryl-substituted aldimines and various alkenes to provide 1,2-dihyro and 1,2,3,4-tetrahydro-quinolines using 1,7-sigmatropic rearrangement with induction of chirality. Mild reaction conditions, simple experimental procedure, good yields of products, and optical active induction render this new method attractive for 1,7-sigmatropic rearrangement of imino Diels–Alder reaction.